Therapeutic efficacy trial of artemisinin-based combination therapy for the treatment of uncomplicated malaria and investigation of mutations in k13 propeller domain in Togo, 2012–2013. (December 2016) - Dorkenoo, Améyo; Yehadji, Degninou; Agbo, Yao; Layibo, Yao; Agbeko, Foli; Adjeloh, Poukpessi; Yakpa, Kossi; Sossou, Efoe; Awokou, Fantchè; Ringwald, Pascal
Abstract Background Since 2005, the Togo National Malaria Control Programme has recommended two different formulations of artemisinin-based combination therapy (ACT), artesunate–amodiaquine (ASAQ) and artemether-lumefantrine (AL), for the treatment of uncomplicated malaria. Regular efficacy monitoring of these two combinations is conducted every 2 or 3 years. This paper reports the latest efficacy assessment results and the investigation of mutations in thek13 propeller domain. Methods The study was conducted in 2012–2013 on three sentinel sites of Togo (Lomé, Sokodé and Niamtougou). Children aged 6–59 months, who were symptomatically infected withPlasmodium falciparum, were treated with either AL (Coartem®, Novartis Pharma, Switzerland) or ASAQ (Co-Arsucam®, Sanofi Aventis, France). The WHO standard protocol for anti-malarial treatment evaluation was used. The primary end-point was 28-day adequate clinical and parasitological response (ACPR), corrected to exclude reinfection using polymerase-chain reaction (PCR) genotyping. Results A total of 523 children were included in the study. PCR-corrected ACPR was 96.3–100 % for ASAQ and 97–100 % for AL across the three study sites. Adverse events were negligible: 0–4.8 % across all sites, for both artemisinin-based combinations. Upon investigation of mutations in thek13 propeller domain, only 9 (1.8 %) mutations were reported, three in each site. All mutant parasites were cleared before day 3. All day 3 positive patients were infected withk13 wild type parasites. Conclusions The efficacy of AL and ASAQ remains high in Togo, and both drugs are well tolerated. ASAQ and AL would be recommended for the treatment of uncomplicated malaria in Togo.